Internalisasi Nilai Maqashid al-Syariah dalam Pemahaman Kewajiban Haji Berbasis Al-Qur’an - Arif Zunaidi; Maya Sari Wardani; Saudiah Ayu; Luthfiatunisa Luthfiatunisa; Fachrial Lailatul Maghfiroh (LPPM Universitas Al-Khairiyah, 2026)
A community service activity themed “Internalization of Maqashid al-Syariah Values in Understanding the Obligation of Hajj Based on the Qur'an” was held at the Al Akbar Mosque in Surabaya on Thursday, November 6, 2025. This program was attended by lecturers, students of STAI Al-Akbar, and the community around the mosque. The main objective was to help participants understand the obligation of Hajj not only as a ritual of worship, but also as a practice that has a strong foundation in the Qur'an and contains messages of benefit in accordance with the principles of Maqashid al-Syariah. This activity used a community education approach through a combination of interactive lectures, group dialogues, and guided reflection. Lectures were used to provide a textual foundation of the verses on Hajj and an explanation of the Maqashid al-Syariah framework. Group dialogues helped participants link these concepts to their daily religious experiences, while guided reflection sessions encouraged them to develop a deeper understanding of the values of protecting religion, soul, mind, offspring, and wealth in the Hajj pilgrimage. The results of the activity showed an increase in participants' understanding of the objectives of Sharia in the obligation of Hajj and a growing awareness of the wisdom of this worship for personal and social life. This program is expected to become a model of religious education that strengthens text-based Sharia literacy and values for the mosque community.